2016
DOI: 10.1155/2016/4353604
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity Effects of Hydroethanolic Extract of Jacaranda decurrens Leaves

Abstract: Obesity is a worldwide epidemic that reduces life expectancy; therefore, the search for new alternative and effective treatments is ongoing. The aim of the present investigation was to identify the chemical compounds in the hydroethanolic extract of leaves of Jacaranda decurrens subsp. symmetrifoliolata and to evaluate their toxicity and antiobesity effects. High-performance liquid chromatography was used to identify the chemical constituents, and acute toxicity was evaluated in rats treated with doses of 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, quercetin acts positively on modulation of the TGF-β signaling pathway, favoring healing [46]. ese flavonoids are also present in propolis [47], which has healing and anti-inflammatory activity, as in other plants of Jacaranda genus [48,49]. ere was an increase in type I collagen gene expression in the FtEHJ group compared to the others, although type III collagen gene expression was not different between the groups.…”
Section: μMmentioning
confidence: 99%
“…However, quercetin acts positively on modulation of the TGF-β signaling pathway, favoring healing [46]. ese flavonoids are also present in propolis [47], which has healing and anti-inflammatory activity, as in other plants of Jacaranda genus [48,49]. ere was an increase in type I collagen gene expression in the FtEHJ group compared to the others, although type III collagen gene expression was not different between the groups.…”
Section: μMmentioning
confidence: 99%
“…For insecticidal activity we found no reports in the literature, especially in P. xylostella. Jacaranda decurrens has ursolic acid as a secondary metabolite (Santos et al, 2012;Antunes et al, 2016), isolated by Varanda et al (1992), who observed the reproductive rate, survival, and population growth rate of Schizaphis graminum (Hemiptera: Aphididae) (wheat aphid), one of the main pests of wheat (Gomes et al, 2004), which decreased at direct proportion with the ursolic acid content used in the diet. Terpenes, also described for J. decurrens and J. mimosifolia (Sidjui et al, 2016), have current ecological importance as plant protection agents (Viegas Júnior, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The folk medicine indicates their roots as blood depurative, in the healing of uterine and ovarian wounds, and in the treatment of rheumatic problems and dysentery. Recently reports indicate the anti-inflammatory effect of the carobinha roots and the anti-oxidative, anti-tumoral and anti-obesity activities of its leaves [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%